Verspera, du plan d’époque à la visite virtuelle : une fructueuse collaboration interdisciplinaire - Michel Jordan; Delphine Desbourdes; Nicolas Priniotakis; Wassim Swaileh; Benjamin Ringot; Mathieu da Vinha (Humanités Numériques)
Research in cultural heritage sciences is an interdisciplinary work. In the Verspera project, historians, archivists, curators and computer scientists worked together on the very rich corpus of the Ancien Régime plans of the Château de Versailles. The Verspera project aimed to digitise, preserve and share this corpus with the general public, and to exploit it as 3D models and virtual visits. This paper summarises the different stages of the project and emphasises the breadth and interest of interdisciplinary work for the study of such a cultural heritage object.